2021
DOI: 10.1177/11795727211064156
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Vector Pattern and Biomarkers of Physical Functioning of Prostate Cancer Survivors in Rehabilitation

Abstract: Background: Knowledge of clinically established factors of physical function such as body composition, bioelectrical phase angle (PhA) and handgrip strength (HGS) with mortality predictive and health-related relevance is limited in prostate cancer survivors (PCS). Therefore, the aim of this study was to characterise and compare body composition data of PCS with extensive reference data as well as to analyse PhA and HGS and the prevalence of critical prognostic values at an early stage of cancer survivorship. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The validity of the method extends from prognosis to therapeutic procedures [ 71 , 72 , 73 , 74 ]; BIVA is useful in diseases requiring diuretic therapy, for the detection of fluid overload and the identification, monitoring, and therapy planning of renal patients with impaired fluid balance. However, the greater potential of the method has been found in those patients in whom basal impedance vectors had already been measured under healthy conditions [ 26 , 75 ]; In patients with average and mild obesity, BIVA was proved to be a valid method of analysis, both prognostic and therapeutic. Nonetheless, significant limitations of BIVA method in morbid obesity type III have been detected as the underestimation of body fat percentage and overestimation of FFMv [ 58 , 59 , 60 , 79 ]; in extreme interventions for the treatment of obesity, such as bariatric surgery, BIVA was shown to be useful in highlighting a loss of FM, as well as of FFM [ 78 ]; on the other hand, following therapeutic fasting, the aforementioned limitations were confirmed in the evaluation of subjects with severe obesity [ 79 ]; In the assessment of the body composition of subjects with anorexia nervosa, BIVA assumes considerable importance at the psychological level, while the results show significant limitations for BIA [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity of the method extends from prognosis to therapeutic procedures [ 71 , 72 , 73 , 74 ]; BIVA is useful in diseases requiring diuretic therapy, for the detection of fluid overload and the identification, monitoring, and therapy planning of renal patients with impaired fluid balance. However, the greater potential of the method has been found in those patients in whom basal impedance vectors had already been measured under healthy conditions [ 26 , 75 ]; In patients with average and mild obesity, BIVA was proved to be a valid method of analysis, both prognostic and therapeutic. Nonetheless, significant limitations of BIVA method in morbid obesity type III have been detected as the underestimation of body fat percentage and overestimation of FFMv [ 58 , 59 , 60 , 79 ]; in extreme interventions for the treatment of obesity, such as bariatric surgery, BIVA was shown to be useful in highlighting a loss of FM, as well as of FFM [ 78 ]; on the other hand, following therapeutic fasting, the aforementioned limitations were confirmed in the evaluation of subjects with severe obesity [ 79 ]; In the assessment of the body composition of subjects with anorexia nervosa, BIVA assumes considerable importance at the psychological level, while the results show significant limitations for BIA [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on 58 patients undergoing three-week inpatient rehabilitation after acute prostate cancer therapy included BIVA and hand grip strength test (HGS) at the beginning and end of treatment. The BIVA model and the prevalence of critically low Phase angle values highlight the need for intensive rehabilitation and stand as a valuable aid in personalizing and optimizing the treatment [ 75 ].…”
Section: Bia Application In Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…RA patients have been reported to undergo changes in body weight, arm circumference, waist circumference, hip, resistance/height, reactance/height, and erythrocyte sedimentation rate, which can result in increases in whole-body impedance [28] . An observational study indicated that the regular evaluation of body composition provides a chance to stratify the risk of PCa and may aid in customizing and improving treatment in the rehabilitation and continued survivorship care [29] . Therefore, the main focus of this research is to investigate whether RA increases the risk of PCa through the pathway of impedance of whole body.…”
Section: Discussionmentioning
confidence: 99%